Main controlling factors and development model of tight reservoirs in the Shihezi Formation-Shanxi Formation in the Ordos Basin: Taking the Binchang area as an example - Song LI; Liyuan MA; Ruyue WANG; Jie DENG; Yudong LI; Xiaoyuan QUAN; Rong JIANG (地质科技通报, 2024)
Objective Defining the distribution of sweet spots in tight reservoirs is the focus of tight oil and gas exploration. Methods Using core observation, thin section identification, X-ray diffraction, homogenization temperature measurements of inclusions, and conventional physical property analysis, the sedimentary characteristics, reservoir characteristics, and diagenesis of Upper Palaeozoic tight sandstones in the Binchang area, southern Ordos Basin were studied in detail.The main controlling factors of reservoir formation were identified and the development model of high-quality reservoirs was established. Results The results show that sedimentary facies are the basis of reservoir formation, and the core beach microfacies of the braided river delta plain have coarse grain sizes, small pore-medium-fine throat pore structures, and relatively good reservoir physical properties. The underwater distributary channel and estuary bar in front of the meandering river delta have fine grain sizes and pore throat structures of micropore-microat throat pore structure, and the reservoir's physical properties are relatively poor. Diagenesis plays an important role in controlling the development and distribution of high-quality reservoirs. Intermittent volcanic tuff is transformed into kaolinite in acidic strata and altered into chlorite sheaths in alkaline strata, which inhibits quartz overgrowth and calcite cementation and protects the reservoir space. The secondary enlargement of quartz is mainly caused by the leaching of SiO2 from mudstone to sandstone.The main reasons for the cementation of calcite roof and floor are the filling of feldspar and the dissolution of cuttings in the middle and late stages of calcite. The microfractures formed by late tectonic transformation have no calcite cementation, which improves the physical properties of the reservoir and plays an adjusting role in the gas reservoir. There are two solution pore development zones near burial depths of 3 750 m and 3 900 m in the Binchang area. The optimal reservoir is the medium-coarse-grained sandstone rich in chlorite mantle formed by the transformation of volcanic tuffaceous matter in the dissolution pore development zone. The sub-optimal reservoir is mainly distributed in the middle and lower parts of the sand body with a greater single-body thickness, cyclicity and no mudstone interval in the dissolution pore development zone.This zone is composed mainly of medium-coarse-grained sandstone lacking chlorite film, calcite cementation and secondary enlargement of quartz are the lowest. Conclusion These research results further increase the understanding of the genesis of the development of high-quality tight sandstone reservoirs in the Upper Palaeozoic, providing important guidance for natural gas exploration and development in this area.